2018
DOI: 10.1371/journal.pone.0195863
|View full text |Cite
|
Sign up to set email alerts
|

Variation in energy sorghum hybrid TX08001 biomass composition and lignin chemistry during development under irrigated and non-irrigated field conditions

Abstract: This study was conducted to document the extent and basis of compositional variation of shoot biomass of the energy Sorghum bicolor hybrid TX08001 during development under field conditions. TX08001 is capable of accumulating ~40 Mg/ha of dry biomass under good growing conditions and this genotype allocates ~80% of its shoot biomass to stems. After 150 days of growth TX08001 stems had a fresh/dry weight ratio of ~3:1 and soluble biomass accounted for ~30% of stem biomass. A panel of diverse energy sorghum genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 61 publications
5
27
0
2
Order By: Relevance
“…Previous studies reported different extents of relationships between stem size (mainly height) and lignocellulosic composition and suggested they are genetically and/or physiologically linked (Trouche et al, 2014). McKinley et al (2018) and Perrier et al (2017) reported a decrease in stem cell wall content to the benefit of nonstructural carbohydrate in biomass sorghum but they did not evaluate the genotypic variability of this response. Some studies demonstrated, however, in the case of sweet sorghum (characterized by sweet, juicy, and tall stems), that drought did not affect [postflowering stress ] or even increased [preflowering stress (Almodares, Hotjatabady, & Mirniam, 2013;Perrier et al, 2017)] stem soluble sugar content.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies reported different extents of relationships between stem size (mainly height) and lignocellulosic composition and suggested they are genetically and/or physiologically linked (Trouche et al, 2014). McKinley et al (2018) and Perrier et al (2017) reported a decrease in stem cell wall content to the benefit of nonstructural carbohydrate in biomass sorghum but they did not evaluate the genotypic variability of this response. Some studies demonstrated, however, in the case of sweet sorghum (characterized by sweet, juicy, and tall stems), that drought did not affect [postflowering stress ] or even increased [preflowering stress (Almodares, Hotjatabady, & Mirniam, 2013;Perrier et al, 2017)] stem soluble sugar content.…”
Section: Introductionmentioning
confidence: 97%
“…A significant genetic diversity was pointed out for these traits (Kholová et al, 2014;Vadez, Deshpande, et al, 2011;Vadez, Krishnamurthy, Hash, Upadhyaya, and Borrell, 2011). The effect of drought on the production of biomass sorghum was by far less studied, although a few studies reported biomass sorghum is more drought tolerant than other biomass crops as maize (Schittenhelm & Schroetter, 2014) and that drought reduced stem biomass cell wall content (McKinley et al, 2018;Perrier et al, 2017). The quality of biomass sorghum production relies on stem biomass lignocellulosic composition, soluble sugar content, and digestibility (Trouche et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of biomass derived from forage, grain, and sweet sorghums has been well characterized [28]. The research on exploiting forage sorghum as biofuel was initiated in 1980s, which led to the development of photoperiod-sensitiveenergy sorghum hybrids [29].…”
Section: Analyzing Biomass Stem Compositionmentioning
confidence: 99%
“…Such sorghums exhibit wide variations in biomass composition [34]. Now a days, near-infrared spectroscopic (NIR) analysis is routinely used for high-throughput computation of biomass composition [28].…”
Section: Analyzing Biomass Stem Compositionmentioning
confidence: 99%